How radiative transfer models can support the future needs of earth-system forecasting and re-analysis. (August 2020) - English, Stephen; Lean, Peter; Geer, Alan
Abstract: This paper discusses the role of the observation operator in data assimilation and how the evolving strategy of Numerical Weather Prediction is creating new challenges for Radiative Transfer Model developments, placing an increasing demand on these models and their consistency, bias characterisation and range of capabilities. The paper concludes that to meet future challenges models will need to be developed in a modular style taking elements from many research groups, giving attention to consistency of physical assumptions, interfaces and coding standards.